La practica coral en el proceso de enseñanza-aprendizaje de los estudiantes del primero y segundo años de bachillerato del instituto tecnológico superior 12 de Febrero de la ciudad de Zamora provincia de Zamora Chinchipe. periodo 2013 – 2014 - Narvaez Alba, Carlos Ernesto (2016)
Choral singing is a very important tool to contribute to the educational development of students, for this present research topic was raised, whose main objective is to contribute to the process of teaching and learning of students in the first and second years of high school at the Institute technological Superior "February 12", through choral practice; for this methods that allowed study data using different techniques and instruments such as the interview applied to the rector and professor of aesthetics of the institution culture, and the survey applied to 96 students, where a total of 98 people, which was used the population which worked throughout the research process, the results found that 86% of students have knowledge of classical music, 72% of students have no knowledge or singing a chorus; these gave a better understanding of the problem, the authorities have no knowledge or information about the educational benefits that has a choral group, which allowed to raise a proposal that was the conformation of the choir of the institution. It is concluded that there is much ignorance and lack of interest in terms of the benefits that can be developed with the teaching of choral singing, therefore, recommended to the authorities, and teachers of aesthetic culture take into account this information the benefits that can be developed with choral singing, mainly to strengthen the educational, cognitive, and cultural students in social and personal.